The Reflection of Different Educational Approaches on Life Skills: Waldorf Pedagogy and Montessori Method - Tutar, Nurcihan; Temel, Zeynep Fulya (Gaziosmanpasa University, 2025)
The aim of this research is to determine the place of life skills in Waldorf pedagogy and the Montessori method, as well as to identify educational practices that support life skills. A descriptive qualitative design was chosen because there wasn't enough specific information about how Waldorf pedagogy and the Montessori method help with life skills. Descriptive qualitative design is used with the aim of complementing and explaining the quantitative dimension of studies conducted with mixed methods. The study group consisted of 13 teachers working in the preschool education level of Waldorf and Montessori schools. The interview technique was used for the purpose of sharing experiential knowledge. Criterion sampling, one of the purposive sampling methods was used to determine the study group. In this study, teachers' opinions on twelve life skills were gathered. During the interview, audio recordings were made with the participants' knowledge, and subsequently, a transcript was created. According to the study, the Waldorf method uses random, inwardly focused, nature-based, and cyclical ways of teaching, while the Montessori method uses social, real-life experience-based, and more structured ways of teaching. In the research results, it is interesting to note that the Waldorf method and the Montessori method had fewer teaching activities about how to avoid dangerous situations and what to do in an emergency than they did about other life skills. According to the research, Waldorf pedagogy and the Montessori method are both based on the philosophy of anthropology, but they have different ways of teaching preschool. However, both teach kids skills that will help them in their future lives. It is suggested that in future research, the study group should be met before the study to improve the interview method, different ways of teaching life skills in preschool should be looked at, and finally, this study should be repeated during the Covid-19 period after the pandemic and the results should be compared.
Keywords: Yaşam Becerileri; Waldorf; Montessori; Okul Öncesi Eğitim; Early Childhood Education; Life Skills; Waldorf; Montessori